Optimization of the Unit Resum Performance in the Settlement of the Crime of Vehicle Theft for Realizing Fair Law Enforcement in Polres Sukoharjo - Alamsyah, Athallah Thoriq (Indonesian Journal of Police Studies, 2024)
The objective of the reseach to describe the methods and resources of the Sukoharjo Police Criminal Investigation Common Crime Unit in solving the crime of vehicle theft in order to enforce a justice law. This research is also expected to be a reference for the Sukoharjo Police Criminal Investigation Unit  in determining policies and considering steps in solving the crime of vehicle theft. This research used management theory and organizational resources as  analytical method. Furthermore,  SWOT theory also to be used to determine factors influence the problems The concepts which used in this research are the concepts of optimization, performance, and fair law enforcement. This research used a qualitative method with interviews, observation, and document studies as collection data techniques. The research was carried out in the Sukoharjo Police Station in accordance with the research subject, Sukoharjo Police Criminal Investigation Common Crime Unit. The results showed that in management of investigations for the crime of vehicle theft in the Sukoharjo Police, the resum unit consisted of two sub-units of interrogation and one sub-unit of probation. However, there was no assignment letter of investigation, investigation plan, and budget plan in the preparation of the investigation. In addition, the quality of the rooms at the resum unit is not good enough due to cramped conditions. The support from citizen in eradicating the 3C case in the Sukoharjo was an additional strength for the police in carrying out into criminal acts of theft. One form of support is by giving any information about the case via whatsapp and Instagram belonging to the Sukoharjo Police.